ANALISIS CLASSROOM CLIMATE PADA UJI COBA PEMBELAJARAN TATAP MUKA (PTM) SAAT PANDEMI COVID-19 - Raiza Aulia (Universitas Negeri Padang, 2023)
This pandemic has changed all aspects of life, including the education system. The education system in Indonesia immediately turned online because it could not be done face-to-face. Gradually, the government began to study to restart new normal and conduct face-to-face trials for students, especially high school students in Surabaya. The data collection technique used interviews with students as participants and teachers as a significant other. The author takes the context of classroom climate because face-to-face learning trials are still being reviewed by the local city government to regulate the course of learning in accordance with health protocols. There are three dimensions in the classroom climate, namely relationships, personal growth and development and system changes and improvements. The results of the student interviews showed that they were uncomfortable with face-to-face learning because they felt awkward, uncomfortable in entering the classroom and needed to adapt directly to the teacher, while according to the teacher, the students were very enthusiastic about the face-to-face learning trial.